Intravascular Ultrasound: Principles and Cerebrovascular Applications - Zacharatos, H.; Hassan, A.E.; Qureshi, A.I. (American Journal of Neuroradiology, 2010)
SUMMARY: Intravascular sonography is a valuable tool for the morphologic assessment of coronary atherosclerosis and the effect of pharmacologic and nonpharmacologic interventions on the progression or stabilization of atherosclerosis. An analysis of the different modes, applications, and limitations is provided on the basis of review of existing data from multiple clinical case studies, trials, and mechanistic studies. Intravascular sonography has been used to assess the outcomes of different percutaneous interventions, including angioplasty and stent implantation, and to provide detailed characterization of atherosclerotic lesions, aneurysms, and dissections within the cerebrovascular circulation. Evolution of intravascular sonographic technology has led to the development of more sophisticated diagnostic tools such as color-flow, virtual histology, and integrated backscatter intravascular sonography. The technologic advancement in intravascular sonography has the potential of providing more accurate information prior, during, and after a medical or endovascular intervention. Continued assessment of this diagnostic technique in both the intracranial and extracranial circulation will lead to increased use in clinical practice with the intent to improve outcomes. CIconfidence intervalEELexternal elastic laminaO.D.outer diameter